Photoferroic prospective of multiferroic HoMnO3 compound, evaluated on the base of the DFT study of its magnetic, electronic, and optical properties. (June 2023) - Brito, D.M.S.; Lima, A.F.; Lalic, M.V.
Abstract: In this work, non-collinear spin density functional theory based all-electron full-potential linearized augmented plane wave electronic structure method have been employed to study magnetic, electronic, and optical properties of multiferroic HoMnO3 compound in order to evaluate its potential to be used in photovoltaic applications. Exchange and correlation effects of the Ho 4f- and Mn 3d-electrons were treated on the base of the local spin density approximation including effective Hubbard (Ueff ) correction. We concluded that the ground state magnetic structure should be described by Γ3 irreducible representation of the P63 cm space group, for both the Mn and the Ho magnetic sub-lattices. The calculated indirect and direct band gaps, corresponding to the transition from the O 2p-to the Mn 3d-states, are found to be 1.25 eV and 1.4 eV, respectively, in very good agreement with the experimental findings. Calculated dielectric tensor spectra are found to be in satisfactory agreement with the experiment as well. On the base of these results, we investigated photoferroic properties of the HoMnO3 by calculating its absorption coefficient spectrum and the effective mass tensor of the photogenerated electrons and holes. By comparing results with those of isostructural LuMnO3 and the YMnO3 multiferroics, we concluded that the HoMnO3 exhibits similar photoferroic properties, a fact that classifies it as a material suitable for photovoltaic applications. Highlights: Electronic, magnetic, optical properties of HoMnO3 were studied from first principles. Calculated bandgap and optical spectra agree with the experimental data. Ground state magnetic order is found to be Γ 3 for both the Mn and the Ho sub-lattices. Eventual employment of the HoMnO3 in photovoltaic applications was evaluated. Photoferroic usability of the HoMnO3 is not inferior to that of the YMnO3 and LuMnO3 .